Advancing Security Protocol Verification: A Comparative Study of Scyther, Tamarin - Le, Thi Minh Chau; Pham, Xuan Thang; Le, Vinh Thinh (Journal of Technical Education Science, 2024)
In the dynamic field of Internet security, verifying and analyzing security protocols is crucial for ensuring secure and effective communication. This paper presents an analysis of leading tools used for the verification, falsification, and analysis of security protocols, focusing particularly on Scyther and Tamarin. We examine the methodologies, capabilities, and applications of these tools in various contexts, including cloud computing and IoT, highlighting their unique approaches and contributions to the field. The paper starts with an examination of the Scyther tool, emphasizing its innovative approach to automated falsification and verification, and its application in multi-protocol analysis. We then transition to exploring the use of Scyther in verifying key agreement protocols in cloud computing. A comparative analysis of Scyther and Tamarin is also presented, shedding light on their effectiveness in identifying security properties and revealing the strengths and weaknesses of different protocols. This is further enriched by a detailed look at the unbounded verification capabilities of Scyther. Additionally, the paper covers the capabilities of the Tamarin prover, exploring its advanced features in symbolic analysis, its ability to handle complex security properties, and its application in verifying protocol implementations. Through this paper, we aim to provide a comprehensive overview of the current landscape in security protocol verification, offering insights into the methodologies, challenges, and future directions in this essential area of research.